The isolation of piperine from Piper nigrum L. - Santamaria, Ma. Victoria D.
Piperine crystals isolated from Piper nigrum L. (Fam. Piperaceae) were light yellow, monoclinic crystals melting at 130-131°C. Treatment of piperine with I2 in KI solution yielded steel-blye neeles of piperine periodide. The functional group pipridine and methylene dioxybenzene were found to be present in the crystals. Thin layer chromatography showed an Rf value of 0.35 for an alcoholic solution of the crystal. Visible spectrophotometric analysis showed a maximum absorbance at 780 nm.